Inflammatory myofibroblastic tumor of the right renal pelvis: A case report - Xiaorui Zhu; Xueli Dong; Hongzhou Sheng; Renbin Deng; Xianzhong Duan (Urology Case Reports)
Inflammatory myofibroblastic tumor(IMT) is an uncommon soft tissue neoplasm rarely reported in the urinary tract. A 54-year-old male presented to our institution with low back and abdominal pain, hematuria, and lower urinary tract symptoms for 2 months. We performed abdominal contrast-enhanced computed tomography (CT) and magnetic resonance imaging (MRI), which showed a mass in the right renal pelvis-inferior calyx. Then, we performed the laparoscopic radical nephroureterectomy.